2006
DOI: 10.3171/foc.2006.20.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transforaminal lumbar interbody fusion with unilateral pedicle screw fixation

Abstract: Object Posterior lumbar interbody fusion (PLIF) has been shown to be effective in the treatment of axial low-back pain. Minimally invasive spine surgery for arthrodesis has several advantages, including quicker patient recovery, less postoperative pain, and less destruction of adjacent tissue. The purpose of this paper is to evaluate the clinical outcomes after PLIF procedures in which unilateral pedicle screw fixation was used. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
108
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 13 publications
9
108
1
1
Order By: Relevance
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
“…Our study demonstrated that minimally invasive transforaminal lumbar interbody fusion improved clinical scores in patients with spondylolisthesis and other lumbar degenerative diseases; that the improvements observed were greater than the minimal clinically important difference threshold [2,10], consistent with the standards of arthrodesis outcomes described in the literature [3,4,6,16,17,[19][20][21][22][23][24][25]; and that these improvements were maintained up to 5 years after surgery. Our study also illustrated a challenging learning curve for this procedure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In recent years, there have been several case series and comparative studies on minimally invasive lumbar spine fusions [1,[6][7][8][9][10][11][12][13][14]. In the present study, percutaneous pedicle screw-rod instrumentation was used for MIS-PLF.…”
Section: Discussionmentioning
confidence: 95%
“…Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) has been reported by several authors [1,[7][8][9]14]. Subsequently, Foley et al [4] introduced a percutaneous pedicle screw insertion and rod assembly system (CD Horizon Sextant, Medtronic, Memphis, TN, USA) for MIS-TLIF.…”
Section: Introductionmentioning
confidence: 99%